Proof
- Suppose f is cont on [a,b]
- Consider ∫abf(x)dx
- =limn→∞∑i=1nf(xi∗)△x
- Suppose F is any anti-derivative on [a,b]
- Then, ∀x∈[a,b],F′(x)=f(x) by defn of Antiderivative
- Since F′(x)=f(x), F(x) is Differentiable on [a,b]
- Thus. F(x) is continuous on [a,b] as Differentiability Implies Continuous
- It follows that F(x) is also diffferentiable on (a,b)
- By MVT, ∃c∈(xi−1,xi) s.t f′(ci)=xi−xi−1f(xi)−f(xi−1)
- ⟹f′(ci)=f(xi)−f(xi−1)(△x) by defn of △x
- Note that f′(ci)=F(c)=F(x)∣ba
- Thus, f(xi)−f(xi−1)=F(ci)(△x)
- By MVT, ci∈[a,b]. Choose xi∗=ci
- Now, limn→∞∑i=1nf(ci)△x
- =limn→∞∑i=1n(F(xi)−F(xi−1))
- This is a Telescoping Series, then, you should get after computation: limn→∞F(x0)−F(xn)=limn→∞F(a)−F(B)
- Thus, ∫abf(x)dx=F(a)−F(b)